REVISION DE LAS BENNETTITALES DE LA FORMACION BAQUERO (CRETACICO INFERIOR), PCIA. DE SANTA CRUZ. II. BRACTEAS (Ameghiniana, 2013)
"This is a second part of the Revision of the Bennettitales found in the Baqueró Formation (Lower Cretaceous) of Santa Cruz Province. It deals with the study of the bracts which are refered to the genus Cycadolepis. The following species are described: Cycadolepis coriacea Men., C. involuta Men., C. lanceolata Men., C. oblonga Men., C. menendezii n.sp., C. baqueroensis n.sp., C. petriellai n.sp., C. sp. 1, C. sp. 2. With the present material, 9 species of bracts are known. All main characters are summarized in a table. It is posible to suggest relations among bract species and leaves, already described for the same formation: Cycadolepis oblonga and C. lanceolata whith leaves of Zamites, Cycadolepis involuta whith Dictyozamites latiiolius, C. menendezzi whith Ptilophyllum longipinnatum, C. baqueroensis whith Dictyozamites minusculus. This relations are based on cuticle similarities. Some species have been studied with the Scanning Electron Microscope."